Desmoplastic Small Round Cell Tumor With Ascending Intraspinal Metastasis at Recurrence: Case Report and Review of the Literature. Issue 2 (March 2022) - Cacciotti, Chantel; Samji, Nasrin; Cox, Stephanie; Yikilmaz, Ali; Hann, Crystal; Marin, Jorge A.; Fowler, JoAnn; VanHouwelingen, Lisa; Athale, Uma
Abstract : Background: Desmoplastic small round cell tumor (DSRCT) is a rare and aggressive malignancy commonly involving the abdomen and/or pelvic peritoneum. Despite aggressive therapy, the prognosis remains poor. Central nervous system relapse is rare in abdominal/pelvic primary DSRCT. Observation: We report a case of a 10-year-old female with a large pelvic DSRCT and involvement of the rectosigmoid colon and liver. Following treatment with chemotherapy, and cytoreductive surgery with hyperthermic intraperitoneal chemotherapy an initial response was noted. With progressive lower limb weakness, recurrence with perineural invasion in the lumbosacral nerve root involving the conus was noted 2.5 years from diagnosis. Cerebrospinal fluid showed tumor cells with a molecular confirmation. Conclusions: Perineural invasion and ascending paralysis secondary to primary abdominal DSRCT has not been previously reported to our knowledge. We recommend a high index of suspicion for early and accurate diagnosis of this rare presentation.